Interventions to prevent hypertension in pregnant women: A systematic review - Nayluzzuharo, Fanny; Haryanto, Joni; Nastiti, Aria Aulia (Pediomaternal Nursing Journal, 2024)
Introduction: Pre-eclampsia is one of the serious complications of pregnancy with a high incidence rate, which is about 5-8% in pregnancies worldwide. Although often experienced by pregnant women, the aetiology of pre-eclampsia is still largely unknown. This systematic review article aims to conduct a systematic review of various interventions that have been tested to prevent hypertension in pregnant women. Methods: This systematic review article was conducted based on literature obtained from several databases SAGE Journals, ProQuest, PubMed, Scopus, and ScienceDirect by synthesising relevant research articles on hypertension prevention interventions in pregnant women using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklist method. Results: The research results of this systematic review identified 6 articles published between 2019 and 2024. The articles included in this systematic review included studies conducted in 3 geographical regions, including: Asia, America, and Europe. Some of the interventions included in these studies include the development of educational mobile apps on pre eclampsia for pregnant women, provision of educational tools such as pamphlets and videos, dietary management, and evaluation of low-dose aspirin and probiotics Conclusion: Several hypertension prevention interventions that can be implemented in the care of pregnant women include education on risk factor management, lifestyle modification, and pharmacological therapy. Keywords: pregnancy; pre-eclampsia; hypertension prevention